Enhanced extraction of arsenic and cadmium from environmental samples using a natural deep eutectic solvent and determination by inductively coupled plasma mass spectrometry - Moreira, Luana S.; Santana, Ana P. R. [UNESP]; Costa, Floriatan S.; Vera, Josiane B. [UNESP]; Gonzalez, Mario H. [UNESP]; Silva, Erik G. P. da; Amaral, Clarice D. B. (Taylor & Francis Ltd, 2020)
A natural deep eutectic solvent (NADES) synthesised from malic acid, xylitol, and water was used as a solvent in ultrasound-assisted extraction (UAE) for the determination of As and Cd in fish and shellfish samples by inductively coupled plasma mass spectrometry. The formation of the solvent was confirmed by infrared spectroscopy analysis, which showed the presence of hydrogen bonds between the components. Evaluation was made of elemental determinations performed using standard and kinetic energy discrimination (KED) modes. Higher sensitivity was observed using KED mode, which could be attributed to charge transfer between carbon and the analytes when the NADES introduced into the plasma. The detection limits were 12.7 and 0.100 mu g kg(-1)for As and Cd, respectively, and the accuracy of the extraction procedure was assessed by comparing methods. The Cd concentrations in the fish and shellfish samples were below the limits of quantification, while the As concentrations varied between 1.88 and 12.0 mu g g(-1), exceeding the maximum values recommended by regulatory agencies.
Keywords: Green solvents; natural deep eutectic solvent; ultrasound-assisted extraction; plasma-based technique